Prognostic Value of Novel Liquid Biomarkers in Patients with Metastatic Castration-Resistant Prostate Cancer Treated with Enzalutamide: A Prospective Observational Study. (14th May 2020) - Benoist, Guillemette E; van Oort, Inge M; Boerrigter, Emmy; Verhaegh, Gerald W; van Hooij, Onno; Groen, Levi; Smit, Frank; de Mol, Pieter; Hamberg, Paul; Dezentjé, Vincent O; Mehra, Niven; Gerritsen, Winald; et al.
Abstract: Background: Several treatment options were recently added for metastatic castration-resistant prostate cancer (mCRPC). However, response to therapy is variable, and biomarkers that can guide treatment selection and response evaluation are lacking. Circulating RNAs are a promising source of biomarkers. We explored messenger RNAs (mRNAs), microRNAs (miRNAs), and long noncoding RNAs (lncRNAs) as potential biomarkers in liquid biopsies of patients with mCRPC treated with enzalutamide. Methods: Forty patients were included in this prospective multicenter observational study. Whole blood was drawn at baseline and 1, 3, and 6 months after start of therapy. Four mRNAs, 6 miRNAs, and 5 lncRNAs were analyzed by quantitative PCR. RNA levels in 30 healthy individuals were used as controls. RNA expression data were analyzed by Kaplan–Meier and Cox regression analyses, and the primary end point was progression-free survival. Clinical factors were included in the multivariable Cox regression analysis. Results: Levels of 2 miRNAs, miR-375 and miR-3687, and 1 lncRNA, N -acetylated alpha-linked acidic dipeptidase like 2 antisense RNA 2 (NAALADL2-AS2), were more than 2-fold higher in patients with mCRPC compared with healthy volunteers. Patients with higher levels of miR-375 or miR-3687 showed a shorter time to progression. Patients with higher levels of NAALADL2-AS2 showed a longer time to progression. In the multivariable Cox regression analysis, higher miR-375, miR-3687 and serum prostate-specific antigen concentrations were shown to be independent predictors for shorter time to progression. Conclusions: We identified miR-3687 as a novel prognostic marker for response in patients with CRPC treated with enzalutamide, and we confirmed the prognostic value of miR-375.